Guideline for Chinese tea-packaging: exploring the connection between cultural heritage and the Chinese visual identity representation - Xue, Yang (2025)
Tea packaging in China serves both a functional and symbolic role, reflecting the nation's deep-rooted cultural heritage while influencing consumer choices. Traditionally, tea packaging has been an extension of Chinese identity, incorporating artistic elements that evoke historical and aesthetic significance. However, globalization and evolving consumer preferences have led to a shift in design trends, creating a tension between preserving cultural authenticity and meeting modern market demands. This study then examines the role that tea packaging plays in representing the cultural identity of Chinese heritage while also influencing consumer behaviour. It explores how packaging design elements, including colour, typography, material, and traditional motifs, contribute to consumer perceptions and purchasing intentions. The research applies consumer behaviour theories such as the Theory of Planned Behaviour, the Theory of Reasoned Action, and the Elaboration Likelihood Model to analyse the psychological and cultural impact of packaging design. A quantitative methodology is employed, utilizing structured surveys distributed via digital platforms to ensure a diverse and representative sample. Data analysis through statistical techniques, including regression and correlation analysis, reveals that culturally embedded design elements significantly enhance consumer engagement, emotional response, and brand loyalty. Findings show that packaging aligned with Chinese heritage promotes deeper consumer engagement and has a positive influence on purchasing behaviour. The study also notes a preference for traditional visual elements among consumers while there still being a need for modern design integration. The research contributes to the fields of cultural studies, consumer psychology, and marketing by providing insights into effective packaging strategies that balance cultural preservation with contemporary design trends. Also offered are guidelines for industry professionals to develop packaging that appreciates Chinese cultural identity while enhancing market competitiveness.